Determination Total Creatine Kinase Activity and Creatine Kinase Isoenzymes Activities in Patients with Ulcerative Colitis and Crohn’s Disease under Infliximab Therapy - Mustafa S. Al-timimi; Yasser A. H. Al-Issa; Nawal M. Alkhalidi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Creatine kinase (CK) catalyzes the transfer of a phosphate group from creatine phosphate to adenosinediphosphate, and the CK has three isoenzymes CK-MM, CK-MB and CK-BB. Ulcerative colitis (UC) andCrohn’s disease (CD) they are both conditions characterized by long life inflammation of the gastrointestinalsystem. The Purpose of this study was to determine the total CK activity and CK isoenzymes in patientswith Crohn’s Disease and Ulcerative Colitis under Infliximab therapy. For the UC patients, CD patients andcontrols the CK isoenzyme activities and total CK activity was measured, the three CK isoenzymes separateby suitable ion-exchanger small columns (DEAE-Sephadex A-50 exchanger). The results display Creatinekinase isoenzyme chromatograms of all studied groups (UC, CD patients and controls), with variableactivities of (CK-BB) and (CK-MB) isoenzymes with noted an elevation of (CK-MM) isoenzyme activitiesand significantly elevation total CK activity in serum of patient groups after therapy when compared withbefore therapy patient groups.